Research of the shipwreck near the islet of Gnalić (Gagliana grossa, 1583) (In situ, 2024)
The research of the shipwreck near the Gnalić islet began at the end of the 1960s. After several rescue excavation campaigns the excavation was continued in a systematic form in 2012, under the auspices of the Department of Archeology of the University of Zadar. Access to the main frame, located in the middle of the ship, was cleared in 2021. This year was also marked by continuation of the works on the surface under which the futtocks belonging to the main frame are located, in order to determine the basic shape of the ship. At the end of the research, a lead pilgrim medal with an inscription on both sides was discovered in one of the squares in the central part of the ship (Fig. 5). The inscription seemed completely illegible at the time of the discovery, but preliminary cleaning and conservation enabled its further analysis, which is still ongoing. Although the excavation progressed relatively slowly due to the large amount of ship ballast, this year the central part of the ship was prepared for detailed cleaning in the next research campaign.
Keywords: Gnalić; shipwreck; Modern era; Gagliana grossa